Historiography of Archaeological Sites in the Bograd District of the Republic of Khakassia - Krumshin Anna V. (Поволжская археология, 2025)
The article reveals the importance of the Bograd district as an area of intensive archaeological studies, which has a 300-year history of study, starting from the XVIII century, when the first academic excavations were conducted, with the peak of study in the XX century in connection with the construction of the Krasnoyarsk hydroelectric power station, and to the present moment, when objects of archaeological heritage are identified, during the economic development of land. The Bograd district is distinguished by the localization within the area of a number of archaeological cultures, such as Afanasyevskaya, Okunevskaya, Karasukskaya, Tagarskaya, Tashtykskaya. In addition, on the territory of the Bograd district there is a variety of types of archaeological sites, such as settlements, campsites, barrows, rock art images, etc. Also, to date, the question of further studies, conducting rescue archaeological works in the region in connection with the functioning of the Krasnoyarsk reservoir remains. Monuments in the coastal area may be lost.